2022
DOI: 10.3390/ijms23063246
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Roles of Actin-Binding Scaffold Protein, Ezrin

Abstract: Ezrin is one of the members of the ezrin/radixin/moesin (ERM) family of proteins. It was originally discovered as an actin-binding protein in the microvilli structure about forty years ago. Since then, it has been revealed as a key protein with functions in a variety of fields including cell migration, survival, and signal transduction, as well as functioning as a structural component. Ezrin acts as a cross-linker of membrane proteins or phospholipids in the plasma membrane and the actin cytoskeleton. It also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 101 publications
(112 reference statements)
0
23
0
Order By: Relevance
“…As post-translational factors, ERM proteins contribute to the cell surface localization of several cancer-related transmembrane proteins, such as epidermal growth factor receptor 2 and several drug transporters, by cross-linking them with the actin cytoskeleton [27,29,62,63]. Interestingly, our recent studies demonstrated that among the ERM proteins, ezrin predominantly controls the plasma membrane localization of PD-L1, possibly via molecular interaction, in human adenocarcinoma cells derived from uterine cervix (HeLa) and colorectum (LS180) cells, in which ezrin is expressed at the highest level among ERM, based on DepMap global gene expression analysis and RT-PCR data [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…As post-translational factors, ERM proteins contribute to the cell surface localization of several cancer-related transmembrane proteins, such as epidermal growth factor receptor 2 and several drug transporters, by cross-linking them with the actin cytoskeleton [27,29,62,63]. Interestingly, our recent studies demonstrated that among the ERM proteins, ezrin predominantly controls the plasma membrane localization of PD-L1, possibly via molecular interaction, in human adenocarcinoma cells derived from uterine cervix (HeLa) and colorectum (LS180) cells, in which ezrin is expressed at the highest level among ERM, based on DepMap global gene expression analysis and RT-PCR data [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Ezrin is one of the members of the ezrin/radixin/moesin (ERM) family of proteins [86]. ERM proteins exert numerous physiological functions in morphogenesis, cell polarity, and modulation of cell membrane tension [86].…”
Section: 2mentioning
confidence: 99%
“…Ezrin is one of the members of the ezrin/radixin/moesin (ERM) family of proteins [86]. ERM proteins exert numerous physiological functions in morphogenesis, cell polarity, and modulation of cell membrane tension [86]. All these varied roles are carried out by ERM proteins by regulating the assembly of protein complexes at the cell surface.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Tanaka C. and colleagues opened the issue and investigated the role of ezrin/radixin/moesin (ERM) family proteins, which have a high degree of sequence similarity with each other that crosslinks several cancer-related transmembrane proteins [ 23 , 24 , 25 , 26 ] with the actin cytoskeleton in the plasma membrane localization of PD-L1, utilizing HEC-151 cells derived from the human endometrial adenocarcinoma [ 27 ]. Tanaka C. et al discovered that all three ERM proteins were highly co-localized with PD-L1 in the surface plasma membrane of HEC-151 cells assessed via immunofluorescent staining with confocal laser scanning microscopy (CLSM), and that they interacted with PD-L1, as demonstrated by the immunoprecipitation assay using anti-PD-L1 antibody [ 27 ].…”
mentioning
confidence: 99%